Sizing and Analysis of Grid-Connected Photovoltaic System with Battery Storage - Borhan, Anies Arina Syazwani; Mohamad Nor , Ahmad Fateh (Evolution in Electrical and Electronic Engineering, 2022)
Due to the COVID-19 pandemic, the rise in electrical demand has affected the stability of the power system. Malaysia is a developing country with a huge energy demand and has undergone a lot of efforts to implement renewable energy, especially for power generation. To provide useful grid services and allow high penetration of photovoltaic (PV) systems, battery energy storage systems (BESS) are considered a promising option. This study aims to size and analyze a grid-connected photovoltaic system with battery storage for a residential house, develop a Graphical User Interface (GUI) that can perform sizing of a grid-connected photovoltaic system with battery storage and compare the generated GUI result with the manual sizing result. To test out the hypothesis that a grid-connected photovoltaic system with battery storage leads to a more stable power system, the house’s load data and size are collected, and the GUI is developed using MATLAB software to size the grid-connected photovoltaic system with battery storage. The GUI can size the load consumption and determine of every component, costing and return on investment (ROI) for the grid-connected photovoltaic system with savings battery storage. The result is observed and the generated GUI result must correspond to the manual calculation. These results suggest that the correct sizing is crucial as the total payback period depends on total monthly saving and the total cost of the PV system installation. On this basis, the grid-connected photovoltaic system with battery storage should be considered to achieve more stable power system.